2006
DOI: 10.1183/09031936.06.00112605
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the dogma: novel β2-adrenoceptor signalling in the airways

Abstract: b 2 -Adrenoceptor agonists evoke rapid bronchodilatation and are the mainstay of the treatment of asthma symptoms worldwide. The mechanism of action of this class of compounds is believed to involve the stimulation of adenylyl cyclase and subsequent activation of the cyclic adenosine monosphosphate (cAMP)/cAMP-dependent protein kinase cascade.This classical model of b 2 -adrenoceptor-mediated signal transduction is deeply entrenched, but there is compelling evidence that agonism of b 2 -adrenoceptors can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 276 publications
(319 reference statements)
2
119
1
1
Order By: Relevance
“…Recently, it has been demonstrated that b-adrenoceptors can switch coupling from Gs to Gi [43]; however, since formoterol elevates cAMP in MDM, this is an unlikely explanation in MDM. Alternative b 2 -adrenoceptor signalling pathways have been proposed [44,45]. For example, b 2 -adrenoceptors coupling to Gs can mediate smooth muscle relaxation in a cAMP-independent manner [46,47].…”
Section: Cell and Animal Studies Le Donnelly Et Almentioning
confidence: 99%
“…Recently, it has been demonstrated that b-adrenoceptors can switch coupling from Gs to Gi [43]; however, since formoterol elevates cAMP in MDM, this is an unlikely explanation in MDM. Alternative b 2 -adrenoceptor signalling pathways have been proposed [44,45]. For example, b 2 -adrenoceptors coupling to Gs can mediate smooth muscle relaxation in a cAMP-independent manner [46,47].…”
Section: Cell and Animal Studies Le Donnelly Et Almentioning
confidence: 99%
“…␤ 2 -Adrenoceptor agonists act by binding to the ␤ 2 -adrenoceptor, which activates adenylate cyclase via the signal-transducing G s protein, thereby enhancing cellular cAMP levels and activating protein kinase A. One of the consequences of this signaling is a fall in intracellular calcium and the promotion of smooth muscle relaxation (Giembycz and Newton, 2006). Apart from the affinity for ␤ 2 -receptors, the potency of agonists also depends on the intrinsic efficacy of each compound.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that the β 2 -adrenoceptor can couple via the heterotrimeric stimulatory G-protein (Gs) to adenylyl cyclase (AC) [22]. To evaluate, whether adenylyl cyclase is involved in the action of salbutamol, we employed a pharmacological inhibitor of adenylyl cyclase, SQ-22,536.…”
Section: Effects Of Adenylyl Cyclase and Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…large-conductance calcium activated potassium channel and ATP-sensitive potassium channel) that open upon phosphorylation, resulting in the efflux of K + from the cell down its concentration gradient leading to membrane rectification (repolarisation). Gating of K + channels may also be effected by the direct interaction of G sα with the channel independently of cAMP and PKA [22]. Pharmacological blockade of large-conductance channel (BK Ca ) with charybdotoxin, and the more selective iberiotoxin, prevents hyperpolarisation and β 2 -adrenoceptor-mediated relaxation in smooth muscle cells [22].…”
Section: Role Of Ca 2+ -Activated K + -Channels In the Effect Of Salbmentioning
confidence: 99%
See 1 more Smart Citation